Adsorption of Pb(II) and brilliant green dye onto geopolymer/zeolite hybrid composites - Khalid, Hammad R. (Frontiers in Nuclear Engineering, 2026)
Geopolymers, aluminosilicate materials formed by alkali activation, have drawn interest because of their unique mechanical, chemical, and thermal characteristics. They are interesting for adsorption applications due to their similar chemical structure to zeolite. This study investigates the synthesis and characterization of hybrid geopolymer/zeolite composites to remove lead ions (Pb(II)) and brilliant green (BG) dye from aqueous solutions. Sodium hydroxide and sodium silicate were used to activate fly ash and blast furnace slag blends. This was followed by hydrothermal treatment to encourage the conversion of amorphous geopolymeric gel to crystalline zeolites. Several variables were systematically changed, such as foaming agents, alkali molarity, and bead size to compare adsorption performance. The formation of zeolite phases was confirmed by structural and morphological investigations, such as XRD, FT-IR, SEM, and BET, which also shed light on the porous character of the composite. The geopolymer/zeolite composites demonstrated notable removal efficiency for Pb(II) (up to 123 mg/g) and BG dye (up to 115 mg/g) in adsorption studies. Importantly, this work reveals that average pore diameter plays a more critical role than surface area in determining adsorption capacity of bulk-type adsorbents, contrasting conventional assumptions in the field. The work provides possibilities for creating long-lasting, efficient adsorbents for the treatment of water by highlighting the roles that pore size and surface area play in the adsorption mechanism. Given the structural similarity between heavy metals and certain radionuclides, these findings have broader implications for developing geopolymer-based materials for radioactive waste treatment applications.